Application of Six Sigma method in optimisation design of vehicle anti-explosion components. (April 2023) - Li, Mingxing; Sun, Xiaowang; Zhang, Ming; Wang, Xianhui; Liu, Zhuang; Li, Gaowei; Zhou, Yunbo
With the protection requirements of armoured vehicles continuously improving, the design of anti-explosion components of vehicles is facing increasing challenges. This paper describes a Six Sigma method that is used to optimise the anti-explosion protection components of the vehicle. The thicknesses of some key components of the anti-explosion components and the distributions of the beam are selected as the deterministic design variables. This paper considers the uncertainties in the design process for the failure of the weld and the bolt of the anti-explosion components. The surrogate model generated by the design of experimental (DOE) is combined with the non-dominated sorting genetic algorithm (NSGA-II) to execute the Six Sigma design. Six Sigma design provides the Pareto solution. Lastly, the experiments show that the design based on Six Sigma optimisation is accurate and reliability.